2000
DOI: 10.3171/foc.2000.8.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic hybridization indicating two distinct subgroups of pilocytic astrocytomas

Abstract: Object The authors investigated the spectrum of chromosomal imbalances of pilocytic astrocytoma by using comparative genomic hybridization (CGH). Methods Tumor DNA was extracted from surgically obtained samples of 18 pilocytic astrocytomas that were examined for the presence of neoplastic tissue on frozen sections. Comparative genomic hybridization was performed using standard procedures, and digital ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Gains of 4q and 6q appeared to be more pronounced in biphasic areas, whereas gains of 6 and 8q seemed to be more common in pleomorphic areas. These genetic aberrations are confirmed by CGH studies on homogenized tumor samples in a lower frequency (12)(13)(14)(15) and are also observed in low grade astrocytomas (30). With this specific approach it was possible to show the first evidence of a correlation of different morphologic areas with specific genetic changes.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Gains of 4q and 6q appeared to be more pronounced in biphasic areas, whereas gains of 6 and 8q seemed to be more common in pleomorphic areas. These genetic aberrations are confirmed by CGH studies on homogenized tumor samples in a lower frequency (12)(13)(14)(15) and are also observed in low grade astrocytomas (30). With this specific approach it was possible to show the first evidence of a correlation of different morphologic areas with specific genetic changes.…”
Section: Discussionmentioning
confidence: 62%
“…Comparative genomic hybridization analysis (CGH) showed similar results, affecting several chromosomes including aneuploidy for chromosomes 7 and 8 (12)(13)(14)(15). Fluorescence in situ hybridization (FISH) on isolated nuclei from paraffin embedded material revealed comparable results (16).…”
Section: Introductionmentioning
confidence: 92%
“…Using R-banding and classic cytogenetics, Zattara-Cannoni et al reported chromosomal abnormalities in 13 of 24 cases, including gains of chromosomes 7 and 8 in 3 cases each with a further 6 cases showing random gains or losses (24). A metaphase comparative genomic hybridization (CGH) study reported a pattern of multiple small gains and losses (22).…”
Section: Introductionmentioning
confidence: 99%
“…These gains were not found in one study of low-grade astrocytomas [166], however another study identified trisomy 7 in this tumor type [167]. and 22q [188]. Cytogenetic abnormalities appear unrelated to pediatric low-grade astrocytoma prognosis [189].…”
Section: Medulloblastoma (Mb)mentioning
confidence: 83%